"It was funny at first" exploring tensions in human-animal relations through internet memes with university students. Issue 4 (3rd April 2023) - Tammi, Tuure; Rautio, Pauliina
Abstract: Because of their mostly upbeat everyday presence in most people's lives globally, Internet memes have gained attention as tools in spreading information and enacting attitudinal change in the face of environmental troubles. The reappropriation of memes for classroom purposes is not straightforward, however. We focus our exploration of Internet memes in environmental education to questions of human-animal relations. The context is a higher education course on multispecies childhood studies. The question we pose is whether and how Internet memes can bring forth tensions in human-animal relations. First we review literature mapping what Internet memes are and how they relate to humour and laughter. Then we explore what memes (can) do by creating Internet memes with university students of education. And finally we turn to affect theory and suggest that the potential for environmental education that Internet memes hold, may lie in understanding and using them as feral pedagogical creatures.